2012
DOI: 10.1016/j.eurpsy.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin for the discontinuation of long-term benzodiazepines use: An assessment of its effectiveness in daily clinical practice

Abstract: Our results suggest that pregabalin is an efficacious and well-tolerated adjunctive treatment for benzodiazepine withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 34 publications
0
14
0
4
Order By: Relevance
“…Anecdotally, however, the benefit of the use of pregabalin seems a natural progression; from the evidence relating to alcohol and benzodiazepine withdrawal (Bobes et al, 2012;Nicola et al, 2010).…”
Section: Significancementioning
confidence: 98%
“…Anecdotally, however, the benefit of the use of pregabalin seems a natural progression; from the evidence relating to alcohol and benzodiazepine withdrawal (Bobes et al, 2012;Nicola et al, 2010).…”
Section: Significancementioning
confidence: 98%
“…Two robust studies, a 12-week, prospective, observational, multicenter study including 282 patients [36,68], and a 12-week, randomized, double-blind, placebo-controlled trial including 106 patients [70], have found that PGN is effective in reducing withdrawal and anxiety symptoms, as well as sleep parameters, cognitive and psychomotor functioning, and to a lesser extent it helps in achieving the maintenance of BZD abstinence. According to the studies reviewed, PGN's required dosage range in BD seems to be much higher (by more than 70%) than in AUD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, significant and clinically relevant improvements in withdrawal (p<0.0001) and anxiety (p<0.0001) symptoms, as well as patient's global functioning were observed associated to PGN treatment. The authors concluded that because the improvement in anxiety symptoms in the study, especially the physic symptoms, was clinically relevant as early as the first week, this rapid onset of the anxiolytic effect of PGN may play an essential role in the subsequent success of BZD withdrawal [36,68]. In a secondary analysis of this study, the authors found that PGN was also effective in improving subjective sleep quality in this population group, measured with the Medical Outcomes Study Sleep Scale (MOS Sleep Scale).…”
Section: Pregabalin: Pregabalin (Pgn) (S)-3-(aminomethyl)-5-methyl-mentioning
confidence: 99%
“…Так, J. Bobes и соавт. [7] отметили его эф-фективность при купировании бензодиазепиновой и алкогольной абстиненции, G. Martinotti и соавт. [8], M. Di Nicola и соавт.…”
Section: частота идентификации разных павunclassified